Particle size distribution measurement based on ultrasonic attenuation spectra using burst superposed wave - Nan Jia (Results in Physics, 2019)
In the characterization of particle size distribution (PSD) using ultrasonic attenuation method, the spectrum characteristics such as bandwidth or the number of frequencies is of great significance. To obtain desired attenuation spectra consisting of sufficient information, a direct digital synthesis (DDS) based excitation method has been proposed as burst superposed wave (BSW) featuring in ultrasonic frequencies to be freely defined and component waves’ energy to be artificially controlled. Corresponding experimental systems are designed, in which the traditional pulse wave (PW) and burst single frequency wave (BSFW) are implemented. A pair of broadband ultrasonic transducers with center frequency of 15 MHz is performed to obtain the attenuation spectra of three polystyrene material aqueous suspension (volume fraction 10%). The experimental results show that the traditional methods are unsatisfactory for the relatively large particles. Conversely, BSW can effectively broaden the scope of attenuation spectra and increase the number of frequencies. Afterwards, optimum regularization technique algorithm was used for inversion. The resultant comparisons suggest that the scope and the ultrasonic frequency number of measured attenuation spectra have exerted an obvious impact on the inversion and the BSW technology manifests obvious improvements from the accuracy and reliability of the inversion. Keywords: Ultrasound, Superposed wave, Attenuation spectrum, Frequency control, Particle size measurement